Gendered Existence? Existential-There Construction in English-Polish Translation - Łyda, Andrzej (Lesya Ukrainka Volyn National University, 2021)
This paper analyses a possible effect of the variable of gender on semantic enrichment of existential sentences translated from English to Polish. Existential-there clauses in English typically take the form there + be + indefinite NP (+place/time adverbial). Since there-constructions lack a structurally congruent counterpart in Polish, they can be rendered in Polish with several syntactic constructions ranging from the verb ‘być’ (E. to be) through ‘mieć’ (E. to have) to verbs semantically richer than ‘być’ (e.g., verbs of perception, verbs of location, etc). We ask the question of whether the gender factor is correlated with the factor of text type/genre. To this purpose, we compiled a corpus of English texts representing belles-lettres and popular science writing, male-authored, female-authored and multi-authored and translated by male and female translators. Our preliminary results show that the choice of Polish translations of English existential-there follows from the interplay of genre, narrative/descriptive modes of text, and the gender of the translator, with female translators tending to replace the simple copula ‘be’ with a full lexical verb more often than male translators in dialogic parts of belle-lettres.
Keywords: gender; existential there-clause; translation; English; Polish